Removal of Cr(VI) Ions from Aqueous Solution by Using Syzygium cumini Seeds - Laxminarayana, K.; Laxma Reddy, K. (Asian Journal of Chemistry, 2012)
The present study deals with the removal of Cr(VI) ions from aqueous solution by using Syzygium cumini seeds. Batch adsorption studies showed that Syzygium cumini seeds was able to adsorb Cr(VI) ions from aqueous solutions. The maximum adsorption capacity was found to be 253.16 mg g-1 with 0.1 g of sorbent dosage at pH 2. The effect of pH, contact time, sorbent dosage and temperature have been studied. The adsorption of Syzygium cumini seeds was best fitted by the Langmuir adsorption isotherm and it follows pseudo second order kinetics.